Design and develop a boost converter by using matlab simulink simulation - Norsa’adah Binti Mahmor; Norazila Binti Md Posdzi; Rasidah Binti Abdul Rani (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2020)
This paper presents the design and development of a boost converter by using a resistive load. A booster converter is the most popular application in the industry to step up the direct current (DC) input voltage. This study focuses on determining the suitable value of the inductor and capacitor for use in the circuit. Then, this design focuses on continuous mode operation, with different voltage inputs of 9V and 15V DC, where the switching frequency input is 25kHz using the MOSFET as a switching device. The evaluation of this circuit design is to control the input voltage to keep the output voltage maintained at 24VDC. This analysis also uses a ripple inductor current, not more than 25% of inductor current, and output voltage ripple is less than 1%. The parameters for design circuits based on the output voltage, inductor voltage, and inductor current waveform. The design of this circuit will be analyzed using MATLAB Simulink software to verify the results between simulation and theoretical. Based on the simulation results prove that the developed model can maintain the output voltage by using different voltage input values. Finally, a boost converter circuit can be developing by using these parameters.